PROBLEM-BASED LEARNING TECHNOLOGIES IN TECHNOLOGICAL SCIENCE (Ta'limning zamonaviy transformatsiyasi, 2024)
This article describes the technology of using interactive methods in passing topics that are difficult for students to learn from technology.